Uji Efektivitas Teknik Ekstraksi dan Dry Heat Treatment terhadap Kesehatan Bibit Cabai Rawit (Capsicum frutescensL.) - ASTAWA, I PUTU RINATA; RAKA, I GUSTI NGURAH; MAYADEWI, NI NYOMAN ARI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
ABSTRACT Effectiveness of Technique Extraction Test and Dry Heat Treatment to Seed Health of C hili P epper ( Capsicum frutescens L.). Chili ( Capsicum frutescens L.) is one of the horticultural crops of the Solanaceae family that has a high economic value. Seed healty problems is one of the chili pepperproduction constraints. Chili seeds used by farmers mostly contaminated by seed-borne diseases such as viruses. This study aims to determine the effectiveness of seed extraction techniques and Dry Heat Treatment (DHT) in producing healthy red pepper seeds in a seed source trials of healthy plants and diseased plants. The design used in this research is completely randomized design (CRD) with 2 factors. The first factor was the extraction technique which consist ed of three levels ie extraction technique using 2% HCl, extraction techniques using quicklime and extraction techniques using water. The second factor was DHT with 2 levels ie DHT and without DHT (NDHT). The results of this research showed that DHT treatment was effective in producing healthy chili pepper seedlings with healtinese 100%, while seed extraction techniques has not been effective to produce healthy red pepper seeds with a percentage of less than 90%. Interaction between extraction techniques and DHT on trial seed originating from sick plants showed real influence. Keywords: chili pepper, extraction techniques, Dry Heat Treatment , health y seed